Using next‐generation sequencing to detect oral microbiome change following periodontal interventions: A systematic review - Zhang, Ya; Qi, Yinliang; Lo, Edward C. M.; McGrath, Colman; Mei, May Lei; Dai, Ruoxi (Oral diseases, 2021)
Objectives This systematic review was to evaluate the change of oral microbiome based on next‐generation sequencing (NGS)‐metagenomic analysis following periodontal interventions among systematically healthy subjects. Materials and Methods A structured search strategy consisting of “metagenomics” and “oral diseases” was applied to PubMed, EMBASE, and Web of Science to identify effective papers. The included studies were original studies published in English, using metagenomic approach to analyze the effectiveness of periodontal intervention on oral microbiome among systematically healthy human subjects with periodontitis. Results A total of 12 papers were included in this review. Due to the heterogeneity of selected study, quantitative analysis was not performed. The findings as to how alpha diversity changed after interventions were not consistent across studies. Six studies illustrated clear separation of microbial composition between dental plaque samples collected before and after intervention using principal coordinates/component analysis. The most commonly detected genera before intervention were Porphyromonas, Treponema, Tannerella, and Prevotella, while Streptococcus and Actinomyces usually increased and became the dominant genera after intervention. Correlation network analysis revealed that after intervention, the topology of network was different compared to the corresponding pre‐interventional samples. Conclusion Existing evidence of metagenomic studies depicts a complex change in oral microbiome after periodontal intervention.